Integrating patient information and research data for maxillofacial and craniofacial domain into a single database - Nasaruddin, F.H.; Ismail, M.A.; Nagappan, S. (2010)
Abstract:-Research in the area of maxillofacial and craniofacial surgery almost always comes from images of patients. This paper discusses the possibility of integrating the database for daily medical operational needs together with data for research purposes in the area of maxillofacial and craniofacial surgery. Currently, medical institutions concentrate on systems which have the main function of managing daily operational data. Even at medical institutions where researches are being conducted, data to be used for research are separated from the data from the hospital system. Maxillofacial and craniofacial surgeries are mostly preceded with the development of models, and this nowadays would mean three dimensional digital models This opens an opportunity for medical team to collaborate with other department for example a team from a computer science department. The main task of the CS team is to develop digital models and part of the ongoing research would be on modeling techniques to improve the design of the models. The data from the surgical team can be used the CS team and stored data and models can be reviewed by surgical team to analyze past procedures, diagnoses and prognoses. The design of the database and the system architecture of the proposed system are discussed in this paper. Key-Words:- research database, image data, maxillofacial data, craniofacial modeling 1